Postoperative complications in breast reconstruction with deep inferior epigastric perforator flap: Looking for evidence - Remy, Katya; Sapino, Gianluca; Koch, Nathalie; Raffoul, Wassim; Giordano, Salvatore; di Summa, Pietro G. (Elsevier BV, 2026)
Introduction
This study investigated patient- and surgery-related risk factors of postoperative complications in microvascular breast reconstruction with deep inferior epigastric perforator (DIEP) flaps.
Methods
We reviewed the retrospective charts of 212 patients who underwent 250 DIEP flap breast reconstructions between 2018 and 2023. Patient-related factors included demographic characteristics, comorbidities, radiation therapy, and chemotherapy. Surgery-related factors included reconstructive timing and laterality, perforator choice, venous anastomosis technique, and postoperative acetylsalicylic acid (ASA). Early flap complications (first postoperative week) included flap loss, venous congestion, and hematoma. Late flap complications (after the first postoperative week) included wound dehiscence, skin necrosis, fat necrosis, and infection. Donor-site complications (all late) included wound dehiscence, skin necrosis, infection, seroma, and bulging.
Results
The overall complication rate was 31.1%, and flap loss was 1.9%. Obesity and diabetes were significantly associated with late flap complications and donor-site complications (dehiscence, infection, fat necrosis, and seroma). Radiation therapy showed trends toward greater total flap loss, take back, and flap skin necrosis. Age, hypertension, smoking, and chemotherapy were not associated with higher complications. Harvesting multiple versus a single perforator was associated with significantly more donor-site complications. There were significantly more early flap complications and a trend toward more bulging with lateral versus medial row perforators. Venous anastomosis with a coupler versus a suture showed significantly lower flap complications. Reconstruction timing, laterality, vein number, and ASA use did not impact outcomes.
Conclusion
Complications increased by obesity, diabetes, radiation therapy, and the use of multiple and lateral row perforators, as well as sutured venous anastomoses. Conversely, outcomes were not affected by age, hypertension, chemotherapy, reconstructive laterality and timing, vein number, coupler size, or postoperative ASA use.